Pattern of menstrual cycle after kidney transplant in reproductive women - M. T. Khan; R. Hamid; Sh. Rashid; E. Jahan; N. Lal; R. Ishtiaq (Вестник трансплантологии и искусственных органов, 2022)
Background. In reproductive women, transplant disturbs the menstrual cycle pattern. The two major conditions usually encountered are amenorrhea and menorrhagia.The objective of the study was to assess the pattern of menstrual cycle after kidney transplant in reproductive women.Materials and methods. This cross-sectional study was carried out in a public sector hospital of Karachi, Pakistan. A total 69 patients of reproductive age were included who underwent living kidney donor transplant for more than a year ago. Women having genital tract infection, using hormonal treatment, organic cause of genital tract, clotting disorder and severe cardiac and/ or peripheral vascular disease were excluded. Frequency and percentages were calculated for demographic characteristics. Correlation and association analysis was calculated for type of menstruation with menstrual cycle pattern. A P-value less than 0.05 was considered statistically significant.Results. Majority of female included in the study aged between 35–39 years (36, 52.2%). The most frequent menstrual disturbance observed was heavy menstrual bleeding (22, 31.9%) and amenorrhea (21, 30.4%). Only 2.9% cases showed normal menstrual pattern. The cross tabulation indicated that 26.1% patients had amenorrhea, 24.6% had oligomenorrhea and 31.9% had menorrhagia. The Durbin–Watson value of 0.656 indicated a strong positive relationship between menstruation cycle pattern (dependent variable) and type of menstruation, marital status, donor’s age, children and living location of the patients (independent variables).Conclusion. From the result of the present study, it is concluded that the reproductive age women have shown a disturbed pattern of menstrual cycle after kidney transplant. The major observation was that such patients reported amenorrhea, menorrhagia, oligomenorrhea and hypomenorrhea.